Visible to Near-Infrared Light Integrated Photonic Components on PECVD and LPCVD SiN Platform - Sen Yang; Zuoqin Ding; Xiao Li; Xiao Luo; Shuhua Zhai; Xiujun Zheng; Bo Wang; He Li; Zhuo Deng; Qianshi Wang; Sarp Kerman; Chang Chen (IEEE Photonics Journal)
In this paper, we present our process design kits (PDKs) component performances for different wavelengths in the visible to near-infrared (VIS-NIR) range on Shanghai Industrial μTechnology Research Institute's (SITRI's) 200 mm silicon nitride (SiN) photonics platform. SiN waveguide platform has emerged as a promising technology due to its low optical loss, relatively high refractive index, and transparency across the VIS-NIR spectrum. The industrialization of SiN platforms requires matured PDKs. On SITRI's 200 mm SiN photonics platform, we developed PDKs using both Plasma-Enhanced Chemical Vapor Deposition (PECVD) and Low-Pressure Chemical Vapor Deposition (LPCVD) processes, with SiN layers of 180 nm and 150 nm thicknesses, respectively. The fabricated waveguides exhibit low propagation loss, ranging from 2.5 dB/cm to 0.34 dB/cm from 532 nm to 860 nm. Additionally, we present a low bending loss which is less than 0.06 dB/90° with a radius of 100 μm. Furthermore, the loss of the linear grating coupler (LGC) is less than 2.6 dB at 785 nm. We have also achieved low-loss splitters, including 1 × 2 multimode interference (MMI) coupler, and directional coupler (DC), with a minimum excess loss of 0.03 dB. Additionally, micro ring resonator with high quality (Q) factors of 146,000 has been demonstrated. Our work on developing these PDKs will open new opportunities for researchers and developers to design and fabricate advanced photonic devices on the SiN platform in SITRI's 200 mm fabrication line.